1990
DOI: 10.1115/1.2910365
|View full text |Cite
|
Sign up to set email alerts
|

Porosity and Effective Thermal Conductivity of Wire Screens

Abstract: A simple theoretical model based on combined series and parallel conduction for the effective thermal conductivity of fluid-saturated screens has been developed. The present model has been compared with the existing correlations and experimental data available in literature, and it has been found that the model is effective in predicting thermal conductivity. The study also demonstrates that it is important to include the actual thickness of the wire screen in order to calculate the porosity accurately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(29 citation statements)
references
References 0 publications
2
27
0
Order By: Relevance
“…In the positively inclined and horizontal orientations, the six-layer heat pipe exceeded the maximum power available in the test facility. The maximum heat transport increased with the wick thickness, and is consistent with the results of [15]. For a given heat flux, the liquid velocity in the wick is lower for a thicker wick, and hence results in a lower pressure drop.…”
Section: Effect Of Number Of Mesh Layerssupporting
confidence: 88%
See 1 more Smart Citation
“…In the positively inclined and horizontal orientations, the six-layer heat pipe exceeded the maximum power available in the test facility. The maximum heat transport increased with the wick thickness, and is consistent with the results of [15]. For a given heat flux, the liquid velocity in the wick is lower for a thicker wick, and hence results in a lower pressure drop.…”
Section: Effect Of Number Of Mesh Layerssupporting
confidence: 88%
“…A number of models and correlations for the effective conductivity of wire screen mesh wicks have been developed. These models range from the empirical [10][11][12][13], semi-empirical [14,15], and the analytical [16,17]. The predictions from these models differ by an order of magnitude for the same wick structure.…”
Section: Introductionmentioning
confidence: 99%
“…Since the static and dispersion conduction is relatively small, the related correlations for different geometries are not compared in this study and they can be found in Ref. [21,38,43,44,45]. Ergun et al [20] Packed sphere bed…”
Section: Flow and Heat Transfer Correlationsmentioning
confidence: 99%
“…The thermal conductivity of multiple layers of screen mesh material with the working uid was given by Chang [23] as:…”
Section: Month T ( C) Rh (%) Month T ( C) Rh (%)mentioning
confidence: 99%